The Medicinal Chemistry of Curcuma Longa : A Narrative Review (Bangladesh Journal of Medical Science, 2023)
In Asian nations, the spice curcuma longa (often known as turmeric) is utilised in traditional medicine. Curcumin, which is the most active component, has a lot of therapeutic potential. Turmeric, a rhizome of the Curcuma longa plant, is a more palatable and practical alternative for the average person. It has been proven to have hepatoprotective, anti-inflammatory, antioxidant, antiseptic, antibacterial, and antimutagenic effects. These characteristics make it highly valuable in dentistry, particularly for the treatment of periodontal disease and oral cancer. It aids in the local delivery of medication when used in the gel form. Additionally, it can be utilised in various mouthwash formulations, subgingival irrigants, and pit and fissure sealants. This article looks at its medical uses in dentistry.Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.67-71